The Effect of Using Eniksi Puzzle Media on the Arithmetic Ability of 5-6 Year Old Children - Farah Syifa' Salsabila; Dian Kristiana; Nurtina Irsad Rusdiani (Jurnal Pendidikan Edutama, 2026)
The purpose of this study was to determine the effect of the use of Puzzle Eniksi media on the numeracy skills of children aged 5 to 6 years. Puzzle Eniksi is a learning media specifically designed to help children aged 5 to 6 years to strengthen their numeracy skills by adopting three stages of representation according to Jerome Bruner: enactive, iconic, and symbolic. This study used a posttest-only control group design with a quantitative methodology. All children aged 5-6 years from Al-Kautsar Durisawo Kindergarten, Ponorogo Regency were included in the study population, and samples were taken from two different classes. The instrument used was a numeracy test developed based on indicators. The independent sample t-test was used after the prerequisite tests with homogeneity and normality tests were completed. The findings of the analysis showed that Puzzle Eniksi media significantly improved the numeracy skills of children aged 5 to 6 years. Based on the data, the average score of the experimental group's numeracy ability was 88.77, while the control group's score was 73.00, a difference of 15.77 points. The Sig. value. also shown in the findings of the independent sample t-Test. The null hypothesis (H0) is rejected because the value (2-tailed) is 0.000.